Answer:
(-6 , 5)
Step-by-step explanation:
6x + 10y = 14
6(-6) + 10y = 14
-36 + 10y = 14
10y = 50
y = 5
Answer:
Missing term = 6x
Step-by-step explanation:
We got:
=> 4x by multiplying +4 and x (x * 4 = 4x)
=> 12 by multiplying +4 and +3 (4 * 3 = 12)
=> 2x² by multiplying 2x and x (2x * x = 2x²)
Similarly we will get the "missing term" by multiplying 2x and +3
=> <u>Missing term = 6x, (2x * 3 = 6x)</u>
Hope this helps!
Answer:
2/5
Step-by-step explanation:
3/5 + 1/9
= 12+6/45
= 18/45 which is 2/5
Answer:
Assumptions and bias
Step-by-step explanation:
Creativity and imagination is also not, but assumptions and bias ruin your investigation.